An investigation into the influences of penalty and reward on households’ recycling intention in Federal Territory of Kuala Lumpur / Farshad Amini - Amini, Farshad (2014)
The main objective of this research is to investigate the influences of penalty and reward on households’ intention towards separating recyclable materials at source. People participation in recycling activities is the most important factor of prosperity of recycling programs; therefore investigating recycling from psychological aspect is a proper approach to detect the fundamental factors affecting a successful recycling program. This research used Reasoned Action Approach to investigate the influences of penalty and reward on households’ recycling intention in Federal Territory of Kuala Lumpur. For this purpose, the mediating roles of psychological factors namely attitude, subjective norms, perceived behavioral control, moral norms, situational factors, and consequent of recycling were investigated. 384 questionnaires were distributed and data were analyzed by statistical package for social science (SPSS). Findings showed that, attitude, subjective norms, perceived behavioral control, moral norms, and consequent of recycling partially mediate penalty and reward on recycling intention. Moreover, findings showed perceived behavioral control as the weakest factor affecting recycling intention, also it showed the strong effect from penalty on perceived behavioral control; therefore, based on literature review it is suggested to apply penalty to change behavioral control beliefs in order to increase households’ recycling intention. In Sum, findings of this study show the effectiveness of both penalty and reward to increase recycling intention which is crucial and useful for designing, enforcing, and administrating financial incentive based programs like ‘Pay-As-You-Throw’ in Federal Territory of Kuala Lumpur.